Mitochondrial targeted peptides preserve mitochondrial organization and decrease reversible myocardial changes in early swine metabolic syndrome. Issue 3 (18th December 2017) - Yuan, Fang; Woollard, John R; Jordan, Kyra L; Lerman, Amir; Lerman, Lilach O; Eirin, Alfonso
Abstract: Aims: The mechanisms responsible for cardiac damage in the early stages of metabolic syndrome (MetS) remain unknown. Mitochondria are intimately associated with cellular myofibrils, with the cytoskeleton functioning as a linkage coordinator, and closely associated to the calcium release sites of the sarcoplasmic reticulum (SR). We hypothesized that early MetS is characterized by mitochondria-related myocardial damage, associated with altered cytoskeletal–mitochondria–SR interaction. Methods and results: Domestic pigs were studied after 16 weeks of diet-induced MetS, MetS treated for the last 4 weeks with the mitochondrial-targeted peptide elamipretide (ELAM; 0.1 mg/kg SC q.d), or Lean controls ( n  = 6/group). Cardiac remodeling and function were assessed by fast comuted tomography. Myocardial mitochondrial structure, SR–mitochondria interaction, calcium handling, cytoskeletal proteins, oxidative stress, and apoptosis were studied ex-vivo . MetS pigs developed hyperlipidemia, hypertension, and insulin resistance, yet cardiac function was preserved. MetS-induced mitochondrial disorganization, decreased (C18:2)4 cardiolipin, disrupted ATP/ADP balance, and decreased cytochrome-c oxidase (COX)-IV activity. MetS also increased mitochondrial hydrogen peroxide (H2 O2 ) production, decreased nicotinamide adenine dinucleotide phosphate (NADPH)/NADP and GSH/GSSG, and decreased myocardial desmin and β2 tubulin immunoreactivity, and impaired SR–mitochondrial interaction and mitochondrial calcium handling, eliciting myocardial oxidative stress and apoptosis. ELAM improved mitochondrial organization and cardiolipin species profile, restored ATP/ADP ratio and COX-IV activity, decreased H2 02 production, and improved generation of NADPH and GSH. ELAM also improved cytoskeletal–mitochondria–SR interaction and mitochondrial calcium handling, attenuating oxidative stress, and apoptosis. Conclusions: Disorganization of cardiomyocyte cytoskeletal-mitochondria-SR network is associated with cardiac reversible changes in early MetS, preceding overt cardiac dysfunction. These findings may introduce novel therapeutic targets for blunting cardiac damage in early MetS.